The black beat of Lisbon: Sociabilities, music and resistances - Raposo, O.; Marcon, F. (Exploring ibero-american youth cultures in the 21st century: Creativity, resistance and transgression in the city, 2021)
Since the 1970s, Portugal has established itself as one of the largest migratory flows of Africans to Europe, especially from its former colonies to the Portuguese capital. Gradually, there are numerous precarious and informal construction neighborhoods, with the presence of Angolans, Cape Verdeans, Guineans and Sao Tome, where cultural expressions of the diaspora's musical repertoire are affirmed. From the 2000s, the phenomenon of music digitization contributed to the maintenance of permanent and instantaneous exchanges with what was played and consumed in the countries of origin. New opportunities for crosses and reinterpretations of musical genres have become possible, reinforced by the local senses conferred by young people born and / or raised in Afro-Lisbon producing innovative aesthetic expressions. Started by young blacks, a musical scene with its own circuits of production, circulation and consumption known as "batida" appears in the outskirts of Lisbon, a style influenced by African rhythms, namely Angola's kuduro and electronic music. Djs were the main responsible for affirming this new style, giving this sound a centrality in the market of youth consumption in Portugal and in Europe. Quinta do Mocho is a key neighborhood to understand this dynamics, where from very precarious conditions, some young people took advantage of the opportunities offered by digital devices to create this rhythm, also moving local sociabilities and parties. Home to some of the country's top "batida" Djs, Quinta do Mocho has become an area of intense musical production, where home studios and street parties influence the new global fashions. If some of the DJs in the neighborhood make a music career, most of them do not have the opportunity to make it a full and autonomous profession. In this article, we propose to analyze the trajectories of these young Djs, correlating their life experiences with the transformations that have occurred in the neighborhood and in the musical genre "beat" in recent years. We intend to analyze the relationship between creativity and sociability in music with the resistances built by them in relation to racism, segregation and colonialist forms of social demarcation of existence, space and knowledge.